Water in biochemistry and phisiology - Fuentes Ana M; Amábile Cuevas Carlos F (Instituto Nacional de Pediatría, 2014)
Water plays a crucial role in biology. The H2O molecule has unusual physical chemical properties, due to its structure in liquid state which is still a matter of debate. It establishes hydrogen bonds, between them and with other molecules with electrical charge, which defines the hydrosolubility of such molecules. Prebiotic evolution privileged chemical reactions that occur in water, and their confinement in lipid vesicles, which gave origin to the first cells. Most bio-molecules are water-soluble or amphipathic; water organizes around them in solvation spheres, which have a key role in their biological function. The way water organizes around ions probably explains their intra- or extra- cellular location. In addition to being the solvent for most biochemical reactions, water is also needed or formed by many of them. It is impossible to generalize about the amount of water that humans need to remain healthy. However, thirst is a reliable indicator of the need to drink water. On the other hand, some diseases and some age-groups may not rely entirely on thirst in order to drink enough water; for them it would be necessary to formulate algorithms, rather than allow- ance recommendations. Water is also needed for the disposal of soluble waste through renal function closely regulated by the renin-angiotensin-aldosterone system, that coordinates renal and cardiovascular function, as well as thirst.